Análisis de Amenazas y Vulnerabilidades del Sistema AlquimiaSoft de la Notaria Primera de la ciudad de Babahoyo - Mora Cadena, Estefania Damaris (2019)
The present investigation indicates the billing activities carried out in the First Notary such as: registration of purchase and sale of real estate (car, house, etc.). Electronic invoicing comes hand in hand due to the existing modernization, within this public institution they work with AlquimiaSoft software designed for the registration, control and verification of the information in which all the records that are made daily within the program can be viewed system. The data will be expressed in qualitative terms since they provide a large amount of valuable information that consists in the construction of a theory from a series of propositions extracted, so it is not necessary to extract a representative sample